2011
DOI: 10.3389/fphys.2011.00041
|View full text |Cite
|
Sign up to set email alerts
|

Similar Structures but Different Roles – An Updated Perspective on TLR Structures

Abstract: Toll-like receptors (TLRs) are pattern recognition receptors that recognize conserved structures in pathogens, trigger innate immune responses, and prime antigen-specific adaptive immunity. Elucidation of crystal structures of TLRs interacting with their ligands such as TLR1-2 with triacylated lipopeptide, TLR2-6 with diacylated lipopeptide, TLR4–MD-2 with LPS, and TLR3 with double-stranded RNA (dsRNA) have enabled an understanding of the initiation of TLR signaling. Agonistic ligands such as LPS, dsRNA, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 87 publications
1
68
0
1
Order By: Relevance
“…Residue F126 is located in the core of the (TLR4/MD-2)/(TLR4/ MD-2) oligomerization interface and initiates structural changes in MD-2 upon LPS binding. These conformational changes facilitated hydrogen bonds and electrostatic interactions between the F126 loop residues of MD-2 and a second copy of TLR4, stabilizing the dimeric (TLR4/MD-2)/(TLR4/MD-2) heterotetramer complex (21). Mutation of F126 and the surrounding residues in MD-2 blocked LPS-induced oligomerization (8).…”
Section: Resultsmentioning
confidence: 99%
“…Residue F126 is located in the core of the (TLR4/MD-2)/(TLR4/ MD-2) oligomerization interface and initiates structural changes in MD-2 upon LPS binding. These conformational changes facilitated hydrogen bonds and electrostatic interactions between the F126 loop residues of MD-2 and a second copy of TLR4, stabilizing the dimeric (TLR4/MD-2)/(TLR4/MD-2) heterotetramer complex (21). Mutation of F126 and the surrounding residues in MD-2 blocked LPS-induced oligomerization (8).…”
Section: Resultsmentioning
confidence: 99%
“…27 TLR signaling represents one of the key mechanisms involved in these processes. 28 Although ATF3, an ATF4 homologue, has been reported to participate in the TLR4 signaling pathway 8,29 and recent reports have indicated that ATF4 is capable of regulating cytokine secretion, 9 it remains unclear whether ATF4 plays a role in TLR signaling. In this study, we defined a novel mechanism in which ATF4 is recruited by TLR4 signaling via the MyD88-dependent pathway, translocates to the nucleus and stimulates TLR-triggered cytokine production to further promote an inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…As our understanding of innate immunity has developed, our interest in applying this knowledge to clinical problems has also increased. Most of these translational efforts have been centered on TLRs, which are members of one of the largest and most well-studied family of PRRs (Basith et al, 2011). Moreover, the awarding of the prestigious Nobel Prize in Physiology or Medicine (2011) to Bruce Beutler and Jules Hoffmann for their discoveries concerning the activation of innate immunity underscores the timeliness and significance of this research.…”
Section: Introductionmentioning
confidence: 97%